Intelligently responsive amphiphilic small molecule loaded with doxorubicin to form highly effective anti-hepatocarcinoma nanomicelles - Chunxiao Gao (Elsevier, 2021)
Nanodrug self-assembled by amphiphilic small molecules were proved to be important resource of medicine. In this study, a nanodrug of hydrophobic doxorubicin (DOX)linked to lactose (Lac) via pH sensitive acylhydrazide bond was used as a carrier to entrap the hydrophobic doxorubicin to form drug-loaded nanoparticles (Lac-DOX/DOX). We hope the increased drug to ligand ratio will improve the targeting efficiency of the nanodrug, which leads to better toxicity. The in vitro and in vivo experiments proved that with this nanodrug of Lac-DOX/DOX, we achieved active targeting, passive targeting and physical–chemical targeting through asialoglycoprotein receptor(ASGPR) on liver cancer cells, EPR effect of tumor tissue and acidic tumor microenvironment. This multiple combination can inhibit hepatoma cell proliferation, promote apoptosis, induce immunogenic cell death (ICD) and improve the anti-tumor effect.